Identification of megacerotonic acid and a quinazoline derivative from Universal Natural Product Database as potential inhibitors of Trypanosoma brucei brucei alternative oxidase: molecular docking, molecular dynamic simulation and MM/PBSA analysis. Issue 1 (2nd January 2023) - Adamu, Rahma Muhammad; Ibrahim, Bashiru; Ibrahim, Mohammed Auwal; Balogun, Emmanuel Oluwadare
Abstract: African trypanosomiasis is caused by Trypanosoma brucei subspecies and available drugs against it, are unsatisfactory due to poor pharmacokinetic properties. Trypanosomal Alternative Oxidase (TAO) is an attractive target for anti-trypanosome rational drug discovery because it is essential for parasite-specific ATP generation and absent in the mammalian host. In this study, 360 filtered ligands from the Universal Natural Product Database were virtually screened and docked on T. brucei brucei TAO (PDB-ID 3VVA). From the virtual screening, 10 ligands with binding energy from −10.6 to −9.0 kcal/mol were selected as hits and further subjected pharmacokinetic and toxicity analyses where all of them passed Lipinski's rule of five. Also, the compounds were non-mutagenic, non-tumorigenic and could cross the blood brain barrier. The two topmost hits (UNPD29179; megacerotonic acid and UNPD41551; a quinazoline derivative) interacted with `four glutamates (Glu123, Glu162, Glu213 and Glu266) close to di-iron (2 iron elements) at the catalytic site of the enzyme. Subsequently, 100 ns MD simulations of the two topmost hits were performed using GROMACS where high RMSD values of 0.75 nm (TAO-UNPD29179) and 0.52 nm (TAO- UNPD41551), low residues fluctuations and consistent values of radius of gyration were observed. Moreover, Solvent Accessible Surface Area showed a consistent value of 160 nm 2 for both complexes while TAO-UNPD29179 had higher number of hydrogen bonds than the TAO-UNPD41551. Similarly, MM/PBSA calculations indicated that UNPD29179 had higher free binding energy with TAO than UNPD41551. The data suggest that megacerotonic acid and a quinazoline derivative could be potential inhibitors of TAO with improved pharmacokinetic properties. Communicated by Ramaswamy H. Sarma